Towards large scale microwave treatment of ores: Part 1 – Basis of design, construction and commissioning - Buttress, A.J.; Katrib, Juliano; Batchelor, A.R.; Jones, D.A.; Craig, D.A.; Royal, T.A.; Dodds, Chris; Kingman, S.W. (Elsevier, 2017)
Despite over thirty years of work, microwave pre-treatment processes for beneficiation of ores have not progressed much further than laboratory testing. In this paper we present a scaleable pilot-scale system for the microwave treatment of ores capable of operating at throughputs of up to 150tph. This has been achieved by confining the electric field produced from two 100kW generators operating at 896MHz in a gravity fed vertical flow system using circular choking structures yielding power densities of at least 6x108 W/m3 in the heated mineral phases. Measured S11 scattering parameters for a quartzite ore (-3.69±0.4dB) in the as-built applicator correlated well with the simulation (-3.25dB), thereby validating our design approach. We then show that by fully integrating the applicator with a materials handling system based on the concept of mass flow, we achieve a reliable, continuous process. The system was used to treat a range of porphyry copper ores.